Epilepsia partialis continua - Salam, Abdus; Quddus, Md Ruhul; Sheikh, Md Sayedur Rahman (Bangladesh Medical Journal Khulna, 2015)
Epilepsia partialis continua (EPC) is a rare syndrome of continuous focal jerking of a body part, usually localized to a distal limb, occurring over hours, days or even years. Etiology is multiple and diverse as well as the outcome is also variable. Here we report two cases of EPC admitted almost in a same period in our hospital in Khulna with different etiology and outcome. The first one, an adult diabetic patient, developed status epilepticus followed by right sided epilepsia partialis continua over a period of three days after a viral illness. He responded well with treatment. The second case, a three year old girl, progressively developed epilepsia partialis continua over a period of six months with no antecedent event. Her treatment response is not satisfactory. DOI: http://dx.doi.org/10.3329/bmjk.v47i1-2.22559 Bang Med J (Khulna) 2014; 47 : 25-28